Дослідження пастеризатора молока на імітаційній моделі - Мірошник, В. О.; Лендєл, Т. І. (Energy and Automation, 2017)
STUDY MILK PASTURERS ON THE IMITATION MODEL V. Miroshnik, T. Lendiel Based on the mathematical model of milk pasteurizer, an imitation model was developed using the Simulink MATLAB package. Using the simulation model, studies have been carried out on the influence of process control parameters on the temperature characteristics of milk in different sections of the pasteurizer in a dynamic mode. As a result of experimental and theoretical studies, a dynamic characteristic of the pasteurization section was obtained through the channel "Hot water consumption - temperature of pasteurized milk". The given model will allow to develop algorithms of control of temperature mode for increase of productivity of a pasteurizer. In the simulation model, to study the influence of the process control parameters on the temperature characteristics of milk in different sections of the pasteurizer in a dynamic mode for synthesizing milk temperature control algorithms at the output of the pasteurizer and the recuperator. During the development of the mathematical model of the pasteurizer, the effect of the heat fluxes of the control object was taken into account . Based on the scheme, static balance equations of heat fluxes for the coolant and the product for sections, the values of individual heat fluxes for the pasteurization, recovery and cooling section, and the amount of heat in the individual sections of the sections are compiled. By substituting the equations of individual heat fluxes into the balance equations and differentiating at the initial temperatures of the coolant and the product of each section of the pasteurizer, we obtain a system of six differential equations that describe the dynamics of the heat transfer of the pasteurizer: • in the pasteurization section; • in the recovery section; • in the cooling section. In the simulation model, the object of regulation was investigated through channels for controlling the temperatures of milk cooling and pasteurization. For pasteurization of milk, hot water was used with a temperature of 85 °C, and for cooling ice water with a temperature of 3 °C. The initial temperature of milk from the farm was 25 °C. To maintain the pasteurization temperature of milk, 76 °C spent 0.236 m3 / s of hot water. Based on the mathematical model of milk pasteurizer, an imitation model was developed using the Simulink MATLAB package. Using the simulation model, studies have been made of the influence of the control parameters of the process on the temperature characteristics of the milk in different sections of the pasteurizer in the dynamic mode, which analyzes the effect of the recirculation on the milk temperature at the output of the pasteurizer and the recuperator. This will allow to develop algorithms for controlling milk pasteurization process and provide energy-efficient pasteurizer work.